STUDI ATAS PENYUSUNAN DAN PENGGUNAAN LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN MALUKU BARAT DAYA SEBAGAI SEBUAH DAERAH OTONOM BARU - Sany Heldria Tetmilay (ABIS: Accounting and Business Information Systems Journal, 2014)
Theoretically, financial report has many benefits. However, the phenomenon happened to indicate that the Regional government managing the financial statement is only to comply the terms of legislation. Regional Government has only focuses on getting BPK RI opinion, so that they does not get any advantage from the financial statements.This studyaims to identify andanalyze the level ofunderstanding offinancial managers in MBD Regional District Governmentrelated tothe forminganduse offinancial statements. Data collection techniquesusedisliterature study, documentationand field research.Field researchusedby interviewandobservation.The data obtainedfromthe literature researchandfield researchanalyzed usingqualitativedescriptivemethod. According toMilesandHuberman(1984) inSugiyono(2014: 334) the data analysis process hasdone in threestages: data reduction, data display, and conclusion drawing/verification.The research conducted usingqualitative researchmethodology in designcase studyat MBD Regional District Government. Data analyzedusingthematic analysis. The result showedthat thelevel of understandingoffinancial managementrelated tothe preparationandusingfinancial statementsis still low. This can beseen in theanswers of the resourcewhodo not understand aboutthe preparationandusing offinancial statementsinSKPD. The financial statementshave not beenused effectivelyin thefinancial managementprocess. This caused thelevel of understanding ofthe managementapparatusisstill lowregarding the advantage ofusing thefinancial statements.The analysis alsoshowedthat theencouragement in preparation ofLKPDbasedon the mechanism ofcoerciveisomorphismwhileforming the SKPD financial statementsdrivenby acoerciveisomorphism mechanismandnormativeisomorphism. Encouragementormotivation in use of SKPD financial statements basedon thecoerciveisomorphismmechanism.